Ten years review of cancer bladder in Hospital Universiti Sains Malaysia, Kubang Kerian - Almotawakel, Ahmed Ali Abdullah (2006)
The bladder constitutes the most frequent localization of malignant tumours in the urinary tract and it is one of the common urological malignancies occurring worldwide in both sexes. Local literature on bladder cancer are rather scare and hence the need for a study of this nature. Sixty-seven patients with cancer of the bladder treated in a period of ten years from 1996 to 2005 at Hospital Universiti Sains Malaysia were studied to determine the pattern of the disease and highlight the clinical presentation, cystoscopic finding, histopathology and modalities offered for treatment of the disease. It was found that the mean age of occurrence was 64.5 years. Male to female ratio was 5.7: 1 and predominantly affecting the Malays (86.57%). Sixty-one percent smoker with significant statistical correlation to tumour grade. The most common clinical presentations were haematuria (85.1 %). Transitional cell carcinoma was found in 95.5% of studied population and most patients present with invasive stage (64.2%). TUR was done for 83.6% of them while 28.4% of patients underwent systemic chemotherapy therapy and 4.5% underwent radiotherapy.